Системные факторы в формировании качества отливок - Пелых, С. Г.; Вощенко, А. И.; Пономаренко, Ольга Ивановна; Радченко, А. А. (Белорусский национальный технический университет, 2004)
In the article there is presented the procedure of cast quality control on the basis of concept TQM and analysis of influence of technological, constructive and system factors, and also by examples shown the importance of accounting of system factors in conditions of castings production.
System factors in forming of the casts quality
Keywords: концепция TQM; литейно-технологическая система; дефекты; стержни